An Asian perspective on global financial reforms - Peter J. Morgan; Victor Pontines (Asian Development Bank Institute (ADBI), 2013)
The purpose of this study is to better understand the likely impact on Asian economies and financial institutions of various recent global financial reforms, including Basel III capital adequacy and liquidity rules. Part one reviews the lessons of the global financial crisis (GFC) of 2007-09 and their relevance for Asian economies. Part two describes the major regulatory reforms that have been announced and possible concerns about their impacts on emerging economies. Part three reviews the literature aimed at quantifying the impacts of Basel III capital adequacy rules. Part four develops our methodology and analysis of the quantitative impact of Basel III capital adequacy rules on a panel of Southeast Asian financial institutions with emphasis on the effect on economic growth. Finally, the study concludes with a discussion on the policy implications of the results obtained from the previous section for Asian financial sectors and economies. Overall, we find that the Basel III capital adequacy rules are likely to have limited impacts on economic growth in Asia, but other financial regulations, including liquidity standards and rules for over-the-counter (OTC) derivatives, could have stunting effects on financial development in the region.
Keywords: E17; G01; G18; G21; 330; asian economies; financial institutions; global financial reforms; basel iii; capital adequacy rules; liquidity rules; otc derivatives